2013
DOI: 10.1037/a0030587
|View full text |Cite
|
Sign up to set email alerts
|

Angle-drawing accuracy as an objective performance-based measure of drawing expertise.

Abstract: Drawing expertise is obvious to the eye but the mechanisms underlying such expertise are less well known. An ecological drawing task was analyzed using a novel measure of success, degrees of error on selected angles in the image, which is an objective performance-based measure that was consistent with years of drawing experience. Thirty-three participants drew a complex three-dimensional (3D) still life by direct observation. The more experienced the participants, the more accurate they were at depicting angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…Domain general perceptual enhancement has also been shown in a recent study in which expert artists exhibited superior visual encoding both in rendering and nonrendering contexts (Glazek & Weisberg, 2010). The finding that angular perception correlates with drawing accuracy contrasts with the results of Carson and Allard's (2013) study, in which they reported no correlation between the estimation of planar and projected angles and drawing experience, despite revealing a relationship between perception of slanted angles and drawing experience. The angles used in the current study were most like the planar angles used in their study; however, we avoided using verbal report and instead asked participants to use a visual adjustment procedure with minimal motor demands.…”
Section: Angular and Proportional Perception Predicts Drawing Accuracycontrasting
confidence: 99%
“…Domain general perceptual enhancement has also been shown in a recent study in which expert artists exhibited superior visual encoding both in rendering and nonrendering contexts (Glazek & Weisberg, 2010). The finding that angular perception correlates with drawing accuracy contrasts with the results of Carson and Allard's (2013) study, in which they reported no correlation between the estimation of planar and projected angles and drawing experience, despite revealing a relationship between perception of slanted angles and drawing experience. The angles used in the current study were most like the planar angles used in their study; however, we avoided using verbal report and instead asked participants to use a visual adjustment procedure with minimal motor demands.…”
Section: Angular and Proportional Perception Predicts Drawing Accuracycontrasting
confidence: 99%
“…Similarly, found that context-free angular reproduction accuracy correlated with the drawing accuracy. Drawing experience correlated with the accurate perception of those angles embedded in simple 2D geometric figures or within a complex still life (Carson & Allard, 2013;. This suggests that the relation between perceptual accuracy and drawing ability is not only determined by shape constancy mechanisms, but that reduced susceptibility to angular illusions in general could explain enhanced drawing ability.…”
Section: Errors In Drawing 11mentioning
confidence: 85%
“…It remains unclear whether expertise in drawing is related to the degree of contextual biases in angle perception that are caused by task-irrelevant global properties of the object the angle is embedded (e.g., the degree to which individuals differ in their perceptual judgements of a 60°angle embedded in a cube versus a parallelogram or an isosceles versus a scalene triangle). Such information may further clarify why expert artists and nonartists differ in angle-drawing accuracy (Carson & Allard, 2013) and, more generally, identify the degree to which the transformational processes of visual input that determine our perceptual awareness of the environment can be inhibited.…”
Section: Discussionmentioning
confidence: 99%